Networks of genetic similarity reveal non-neutral processes shape strain structure in Plasmodium falciparum - Qixin He (Nature Portfolio, 2018)
Plasmodium has evolved high genetic diversity in var genes, which encode for the major blood-stage antigen. Here, He et al. show how immune selection shapes the var gene repertoire in both simulated systems and a population in Ghana, by using neutral models and genetic similarity networks.